A Dicobalt Coordination Complex with a Short Cobalt‐Cobalt Distance. Issue 28 (27th July 2018) - Kumar, Jayasree; Gorantla, N. V. T. Sai Manoj; Roy, Sudipta; Paesch, Alexander Noel; Herbst‐Irmer, Regine; Stalke, Dietmar; Anusha, Chakkittakandiyil; De, Susmita; Parameswaran, Pattiyil; Roesky, Herbert W.; Mondal, Kartik Chandra
Abstract: The existence of a metal‐metal bond in organometallic and coordination complexes is a very important aspect. Metal‐carbonyl, carbene‐metal‐carbonyl and metal‐carbene complexes were studied for having this feature. Herein, an air stable dark green color dicobalt coordination complex [Co(III)2 (hep)3 (N3 )3 ] (1) [hepH = 2‐(2‐ethylhydroxy)pyridine] with three μ‐alkoxide bridges has been synthesized and characterized by X‐ray single crystal diffraction, NMR and UV/vis spectroscopy. Complex1 has a short Co⋅⋅⋅Co distance (2.595(6) Å) and thus it has been studied by theoretical calculations. QTAIM (quantum theory of atoms in molecules) as well as EDA‐NOCV analysis (energy decomposition analysis ‐ natural orbitals for chemical valence) do not indicate any significant metal‐metal interaction. The bonding in1 can be best represented by the interaction of two alkokxy bridged valence electrons fragment Co(III)(hep)2 N3 (3d 6 ) with Co(III)(hep)(N3 )2 (3d 6 ) where the donation of the lone pair of electrons from three bridging Ohep ‐atoms stabilizes the dinuclear Co(III) complex. Additionally, thermolysis of1 at 550 o C led to the formation sponge like Co3 O4 oxide. Abstract : An air stable dark green colored complex [Co2 (hep)3 (N3 )3 ]⋅DMF (1⋅DMF) containing a short Co⋅⋅⋅Co distance (2.595(6) Å) has been synthesized and characterized by X‐ray single crystal diffraction and NMR. Nature of Co−Co interactions have been studied by theoretical calculations. Laplacian of electron densities in between two cobalt ions were theoretically evaluated and plotted. Compound1 has been studied by cyclic voltammetry (CV), UV‐vis spectroscopy and thermogravimetric analysis (TGA).1 decomposes to sponge like Co3 O4 oxide when it is heated to 550 o C.